Researching Adverse Childhood Experiences in the Youth Justice System: Reflections on Methodology From a Members of a Non-Indigenous Research Team - Day, Andrew (International journal of offender therapy and comparative criminology, 2023)
Understanding the impacts of Adverse Childhood Experiences (ACEs) has rapidly emerged as an important area of research that has implications for those who work in youth justice settings. This paper identifies a series of considerations facing those who work in jurisdictions where Indigenous or First Nations peoples have much higher levels of contact with both child protection and criminal justice systems than other population groups. It presents some reflections from members of a non-Indigenous research team about their efforts to engage with cultural perspectives on ACEs research in a way that facilitates further discussion within the research community about the methodological decisions that are made when investigating issues that are of importance to members of minority culture communities.